Impact of Rifabutin or Rifampin on Bedaquiline Safety, Tolerability, and Pharmacokinetics Assessed in a Randomized Clinical Trial with Healthy Adult Volunteers - Healan, Amanda M. (Antimicrob Agents Chemother, 2017)
Bedaquiline is a diarylquinoline that specifically inhibits mycobacterial ATP synthase. Bedaquiline has been used to effectively treat tuberculosis (TB) caused by drug-susceptible and drug-resistant Mycobacterium tuberculosis. Rifamycins are a cornerstone of combination drug regimens for the treatment of TB. This phase 1, open-label, randomized, controlled trial evaluated the effect of steady-state dosing of rifabutin or rifampin on the safety, tolerability, and pharmacokinetics of bedaquiline given as a single dose. Thirty-three healthy subjects were enrolled to receive a 400-mg single oral dose of bedaquiline at two time points, on study days 1 and 29. Subjects were randomly assigned to once daily oral doses of rifabutin (300 mg/day, n = 17) or rifampin (600 mg/day, n = 16) during period 2 from days 20 to 41. Serial blood sampling for bedaquiline measurement occurred on days 1 and 29 through 336 h after bedaquiline administration. The day 29 bedaquiline pharmacokinetic parameter estimates were compared to the corresponding day 1 estimates for each rifamycin group. Steady-state rifampin reduced bedaquiline AUC(0–336) approximately 45%, from 47.69 h·μg/ml in period 1 to 26.33 h·μg/ml in period 2. Bedaquiline apparent clearance accelerated 24% in rifampin-treated subjects from 6.59 liters/h in period 1 to 8.19 liters/h in period 2. Steady-state rifabutin resulted in little quantitative impact on bedaquiline exposure but was associated with grade 3 and 4 adverse events before and after the day 29 bedaquiline dose. Dosage adjustments may therefore be necessary to ensure that bedaquiline plasma concentrations reach therapeutic levels safely when combining bedaquiline and rifamycins in TB treatment regimens. (This single-site, randomized, open-label, prospective study in healthy adult volunteers was registered at Clinicaltrials.gov under registration no. NCT01341184.)